3z+6 = 5z+6
3z = 5z
3z-5z=0
-2z=0
z=0
plug it back in to double check
and it does... 6=6
2006-11-27 16:51:27
·
answer #1
·
answered by brandonlsmithe 2
·
0⤊
0⤋
If 3(z+2)=5z+6 then,
3z+6=5z+6 so,
5z-3z=6-6 hence
2z=0 thus
z=0
2006-11-28 01:28:32
·
answer #2
·
answered by Viral M 1
·
0⤊
0⤋
3(z+2) = 5z + 6
sol'n
3(z+2) = 5z+6
3z+6 = 5z+6
3z-5z = 6-6
-2z = 0
-2z/-2 = 0/-2
z=0
CHECKING:
3(0+2) = 5(0)+6
3(2) = 0+6
6 = 6
1. USE DISTRIBUTIVE PROPERTY OF MULTIPLICATION
2. COMBINE SIMILAR TERMS THEN SOLVE
3. DIVIDE BOTH SIDES OF THE EQUATION BY -2 TO CANCEL OUT THE NUMERICAL COEFFICIENT AND TO GET THE VALUE OF THE UNKNOWN, WHICH IS Z
note: if you will transfer a term from one side of the equation to another side then dont forget to change its sign.
if it is (+) then change it to (-) or otherwise, from (-) to (+)
2006-11-28 01:59:00
·
answer #3
·
answered by JHYRA 1
·
0⤊
0⤋
You can't cancel the 6s:
3(z+2)=5z+6[multiply so that you can remove the brackets]
= 3z+6=5z+6
3z-5z=6-6[bring the variables to one side and constant to other side][don't forget to change the sign]
-2z=-0
z=-2\0
=-2
hope you understood
2006-11-28 00:58:53
·
answer #4
·
answered by Lyf's HeCtIC!!!!!!!! 2
·
0⤊
0⤋
3(z+2)=5z+6, distribute the 3
3z + 6 = 5z + 6, subtract 6 from both sides
3z = 5z + 0, subtract 5z from both sides
-2z = 0, divide both sides by -2
z = 0.
Check by plugging 0 in for z in original problem...
3(0+2)=5(0)+6
3(2)=0+6
6=6, it checks out, so the answer is z = 0
2006-11-28 00:58:07
·
answer #5
·
answered by MrDanaH 2
·
0⤊
0⤋
3(z + 2) = 5z + 6 distribute
3z + 6 = 5z + 6 get variables and numbers on opposite sides
-3z - 6 = -3z - 6
0 = 2z divide by 2
z= 0
2006-11-28 00:58:00
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
3(z+2) = 5z +6 distribute 3
3z+6=5z+6 subtract 6 from both sides
3z=5z subtract 3z from each side
2z=0 divide by 2
z=0
2006-11-28 00:56:23
·
answer #7
·
answered by yupchagee 7
·
0⤊
0⤋
After you cancel out the 6's you are left with
3z = 5z
If you were to divide both sides by z, you would be left with
3 = 5, which obviously can't be true.
So 3z = 5z means z = 0.
2006-11-28 00:52:17
·
answer #8
·
answered by oddy411 1
·
0⤊
0⤋
It just doesn't work out. Oh wiat yes it does. Then when you cancel out the sixes you have 3z = 5z. Now that you see that you subtract 3z from both sides to get: 0 = 2z. Now you see that you have to find "what" times 2 equals 0. 0!
2006-11-28 00:50:57
·
answer #9
·
answered by sam 3
·
0⤊
0⤋
3(z + 2 = 5z + 6
3z + 6 = 5z + 6
3z + 6 - 3z = 5x + 6 - 3z
6 = 2z + 6
6 - 6 = 2z + 6 - 6
0 = 2z
0/2 = 2z/2
0/2 = z
0 = z
The answer is z = 0
Insert the z value into the equation
- - - - - - - - - - - - - - - - - - - - - - -
Check
3(z + 2) = 5z + 6
3(0 + 2) = 5(0)+ 6
3(2) = 0 + 6
6 = 6
- - - - - - s-
2006-11-28 07:45:29
·
answer #10
·
answered by SAMUEL D 7
·
0⤊
0⤋
No solution
3(z+2)=5z+6
3z+6=5z+6
3z=5z
z=(5z/3)
(z/z)=(5/3)
1=(5/3)
= No Solution
2006-11-28 00:53:35
·
answer #11
·
answered by Steve 2
·
0⤊
0⤋